Implementasi Kriptografi Dan Steganografi Pada Media Gambar Menggunakan Hill Cipher Dan Least Significant Bit (LSB) - Eka Fitri Jayanti; Wamiliana Wamiliana; Rico Andrian (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2017)
Cryptography can be used to process message using a specific algorithm that make the message difficult to be understood. After that, steganography is used to hide the message in other forms. This research used modified Hill Cipher and Least Significant Bit (LSB) to build a web based application for sending message and get the original message using an android application. The title and cipher key will be sent automatically by the application to the recipient's email. This application can be used by organizations or companies and use stego cover with file type .jpg and message with file type .txt. The modified Hill Cipher and LSB method can be used to encrypt message, embed it to a image and reveal it to the original message. Our research show that the LSB method has the best possibility to reveal message on image manipulated by changing brightness and contrast if the cover in grayscale, and dominant red and white colours image quality.Â